Using photovoice to explore young women's experiences of behaviour change techniques in physical activity mobile apps - Mollie M. Tobin; Tamara L. Jones; Yui Sum Haylie Ho; Camille E. Short (BMC, 2023)
Abstract Background Research shows that inactive young women are attracted to using mobile phone applications (apps) to increase physical activity. Apps can promote physical activity by delivering a range of behaviour change techniques to influence determinants of user behaviour. Previous qualitative research has examined user experiences with techniques in physical activity apps, however there is little research specifically among young women. This study aimed to explore young women's experiences using commercial physical activity apps to change their behaviour. Methods Young women were recruited online to use a randomly assigned app for two weeks to achieve a personal goal. Using photovoice, a qualitative participatory research method, participants generated insights about their experiences through photographs and semi-structured interviews. Thematic analysis was conducted on photograph and interview data. Results Thirty-two female participants, aged 18-24 years, completed the study. Behaviour change techniques tended to cluster around four key themes: logging and monitoring physical activity; reminders and prompts; workout videos and written instructions; and social features. Social support also strongly influenced participants' experiences. Conclusions Results suggest that behaviour change techniques influenced physical activity in line with social cognitive models, and these models are useful to understand how apps can target user behaviour for young women. The findings identified factors important for young women that seemed to moderate their experiences, such as social norms about women's appearance, which should be further explored within the context of behaviour change models and app design.